Dynamic characteristics of SPAD value of rice leaf and adjacent leaf under different N application rates - JIANG Ji-ping; YANG Jing-ping; YANG Zheng-chao; ZOU Jun-liang; GE Chang-shui (浙江大学学报. 农业与生命科学版, 2012)
A field experiment was conducted to investigate the dynamic characteristics of SPAD reading during growth stage of rice and the spatial distribution of SPAD value of four leaves from the top on main stem of rice using the chlorophyll meter SPAD under three different fertilization programs and six different N application rates at tillering stage, booting stage and heading stage of rice. The results showed that the greenness of rice leaf was regularly changed as “black-yellow” alternation ways through the whole growth period of rice, and the sensitivity of the fourth leaf from the top to N was highest, giving it as the most ideal indicator of rice leaf position when using SPAD value to diagnose N status. Furthermore, the difference between SPAD values of the adjacent leaf and nitrogen application rates showed that <inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/j.issn.1008-9209.2012.02.008-I003.jpg"/> was highly related to the plant nitrogen content. With the increasing plant nitrogen content, the difference in SPAD value between the fourth leaf and the third leaf decreased, regardless of fertilizer application condition and development stage. Thus, <inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/j.issn.1008-9209.2012.02.008-I004.jpg"/> value could be used as a suitable indicator for rice plant nutrition status at whole stage.